Integrasi Nilai-Nilai Aswaja dalam Pengembangan Kurikulum Merdeka melalui Pendekatan Deep Learning: Kajian Literatur - Solihah, Faridatus; Sa’diyah, Khalimatus (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
The Merdeka Curriculum provides opportunities for Islamic educational institutions to develop flexible, meaningful, and character-oriented learning. However, its implementation requires the integration of contextual Islamic values to ensure alignment with the objectives of Islamic education. This article aims to examine the development of the Merdeka Curriculum based on Ahlussunnah wal Jama’ah (Aswaja) values through a pedagogical deep learning approach in Islamic Religious Education. This study employs a literature review method by analyzing relevant national accredited journals, books, and educational policy documents. The findings indicate that Aswaja values, which emphasize moderation, balance, tolerance, and justice, are highly compatible with the characteristics of the Merdeka Curriculum. The deep learning approach functions as an effective pedagogical strategy to internalize Aswaja values through reflective, contextual, and student-centered learning experiences. The integration of Aswaja values through this approach positively contributes to meaningful learning, increased student engagement, and the development of moderate and ethical character among learners. Therefore, the development of a Merdeka Curriculum based on Aswaja values through a deep learning approach can serve as a strategic alternative to enhance the quality of Islamic Religious Education.